Evaluation of resectability after neoadjuvant chemotherapy for primary non-resectable colorectal liver metastases: A multicenter study. Issue 2 (February 2016) - Takatsuki, M.; Tokunaga, S.; Uchida, S.; Sakoda, M.; Shirabe, K.; Beppu, T.; Emi, Y.; Oki, E.; Ueno, S.; Eguchi, S.; Akagi, Y.; Ogata, Y.; et al.
Abstract: Background/Aim: The Kyushu Study Group of Clinical Cancer (KSCC) previously reported the safety and efficacy of neoadjuvant chemotherapy with mFOLFOX6 + bevacizumab for H2/H3 liver metastases of colorectal cancer. The aim of the current study was to evaluate the resectability of these metastases before and after chemotherapy as determined by independent liver surgeons. Methods: Between May 2008 and April 2010, 40 patients were registered in a multicenter phase 2 trial of neoadjuvant chemotherapy (KSCC 0802). In Study 1, 5 independent liver surgeons from five different KSCC centers evaluated the resectability of liver metastases of colorectal cancer based on imaging studies performed before and after chemotherapy. Each surgeon was blinded to the other surgeons' evaluations. In addition, no information about the patients' characteristics was provided. In Study 2, 3 surgeons evaluated the resectability of these lesions based on imaging studies with discussion with each other, with the surgeons being provided with information on the patients' characteristics. Results: In Study 1, 13 patients (36.1%) were evaluated to be resectable at baseline, whereas 17 patients (47.2%) were evaluated to be resectable after chemotherapy. In Study 2, 4 patients (11.1%) were evaluated to be resectable at baseline, compared to 23 patients (63.9%) after chemotherapy. Conclusion: Neoadjuvant chemotherapy with mFOLFOX6 + bevacizumab was confirmed to increase the resectability of non-resectable liver metastases of colorectal cancer according to the independent assessments of surgeons.